2019
DOI: 10.1111/scd.12408
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the palate, palatal rugae pattern, and dental arch form in patients with schizophrenia

Abstract: Aims:This study aimed to investigate the morphology of the palate, palatal rugae pattern, and dental arch form in patients with schizophrenia. Methods and results:An observational case-control study was designed following the STROBE statement and checklist. The sample consisted of 132 patients (39 diagnosed with schizophrenia and 93 controls). Dental casts of the patients were classified based on the pattern of their palatal rugae, their dental arch form, and the area of their palate. The palatal rugae in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…From 2016 to 2020, four studies focused on the palate region. Two presented a significant difference in palate width between patients with schizophrenia and healthy controls 26 , 27 , and the other two reported differences in palate shape characteristics but did not find palate width to be significant 28 , 29 . Furthermore, a study measuring the quantitative characteristics of the eyes showed that patients with schizophrenia tended to have smaller optical angles and inner canthal distance.…”
Section: Introductionmentioning
confidence: 79%
“…From 2016 to 2020, four studies focused on the palate region. Two presented a significant difference in palate width between patients with schizophrenia and healthy controls 26 , 27 , and the other two reported differences in palate shape characteristics but did not find palate width to be significant 28 , 29 . Furthermore, a study measuring the quantitative characteristics of the eyes showed that patients with schizophrenia tended to have smaller optical angles and inner canthal distance.…”
Section: Introductionmentioning
confidence: 79%
“…However, none of them used a paired sample in a ratio of 1:2 for the case and control group, respectively. Some authors in epidemiology suggest adding more than one control to each case, as done in the present study, because this feature is capable of optimizing statistical results 10,15 …”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, there are observational case‐control studies that demonstrate several MPA of individuals with schizophrenia compared to the general population 3–9 . On the other hand, there are few studies with specific palate analyses performed in populations with schizophrenia 1,7–10 …”
Section: Introductionmentioning
confidence: 99%
“…The authors also indicate that in the study by Tysiąc‐Miśta et al, 2 the palatal rugae pattern was evaluated. In another study of our group, conducted by Franco et al, 4 we evaluated the palatal rugae pattern and area of patients with schizophrenia. The palatal rugae in patients with schizophrenia had a more random significantly distribution and shape compared to the control group and the palate area was slightly larger in the control group compared with the group of patients with schizophrenia.…”
Section: Conflict Of Intrestmentioning
confidence: 99%